Coady, Amanda. Photograph of South side Cape Broyle, Tom Coady Property and boat with Mindy the cat. - Heritage NL
Amanda Coady provided a picture of Mindy the Cat sitting on a railing post meowing. The picture was taken on Tom Coady's property. A blue pickup truck with a windowed white truck bed cover is parked just beyond the railing on which Mindy the Cat sits. Tom Coady's boat can be seen floating in the harbour in the background.